2014
DOI: 10.3892/or.2014.3404
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GOLPH2 is associated with the progression of and poor prognosis in gastric cancer

Abstract: Golgi phosphoprotein 2 (GOLPH2) has been associated with the development and progression of various human cancers. The aims of this study were to investigate the relationship between GOLPH2 and gastric cancer (GC) progression and explore the clinical significance of GOLPH2 in GC. GOLPH2 expression was examined in four pairs of primary GC tissues and the adjacent non-cancerous tissues from the same patients, using immunohistochemistry (IHC), quantitative PCR and western blotting. Furthermore, GOLPH2 protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…In the present study, we observed that patients with higher GP73 expression have a signi cantly lower overall survival rate than those with low or none GP73 expression, and multivariate analysis revealed GP73 expression was an independent predictor for survival. These results were in accordance with a study of Liu et al, who analyzed the GP73 expression by IHC in 385 gastric cancer patients, and found that GP73 is a useful prognostic variable of overall survival in gastric cancer patients [10]. Our results, with previous reports, may indicate that GP73 may have the potential to be a new target in the treatment of gastric cancer.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we observed that patients with higher GP73 expression have a signi cantly lower overall survival rate than those with low or none GP73 expression, and multivariate analysis revealed GP73 expression was an independent predictor for survival. These results were in accordance with a study of Liu et al, who analyzed the GP73 expression by IHC in 385 gastric cancer patients, and found that GP73 is a useful prognostic variable of overall survival in gastric cancer patients [10]. Our results, with previous reports, may indicate that GP73 may have the potential to be a new target in the treatment of gastric cancer.…”
Section: Discussionsupporting
confidence: 93%
“…A study from Chen et al assessed GP73 protein expression by immunohistochemistry in both tumor and nontumorous gastric mucosal tissue, they found GP73 was down-regulated in gastric cancer, and its expression in gastric cancer was associated with tumor differentiation [9]. Liu et al's study revealed a signi cant correlation between GP73 expression and clinical stage, lymph node metastasis and venous invasion, thus the study made a conclusion that GP73 expression may be associated with tumor progression [10], However, in the present study, no signi cant correlation was found between GP73 expression and clinical variables including age, differentiation and TNM stage, this discrepancy may be explained as the following: rstly, a comparatively more gastric cancer samples was enrolled in the present study, the difference of patient clinical characteristics as a selection bias may in uence the analysis. Secondly, we assessed GP73 expression by IHC on TMA, and it may, to some extent, reduce the experimental bias as compared to IHC on a separate para n tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of GP73 in gastric cancer remains unclear, GP73 was reported to be correlated with tumor differentiation in gastric cancer [9]. Others found the correlation between GP73 and patient survival [10].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, GOLPH2 upregulation was reported in neoplastic and non-neoplastic liver pathologies, and a number of studies postulated its serum level as a novel marker of hepatocellular carcinoma [2,3,4,5,6,7,8]. Subsequently, enhanced GOLPH2 expression was reported in other cancer settings [9,10,11,12,13,14,15]. To the best of our knowledge, GOLPH2 expression in melanoma patients has not been previously analyzed.…”
Section: Introductionmentioning
confidence: 99%